The Pharisees - Sievers, Joseph; Levine, Amy-Jill, 1956- (Grand Rapids William B Eerdmans publishing company, 2021)
"A multidisciplinary appraisal of who the Pharisees were, what they taught, and how they have been understood and depicted throughout history"--
Includes bibliographical references and indexes.
Keywords: Pharisees